Eksplorasi Persepsi dan Praktik Guru dalam Mewujudkan Pendidikan Ramah Anak di Madrasah Tsanawiyah - Andriyani, Santi; Hamidaturrohmah, Hamidaturrohmah (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose –This research aims to describe teachers’ perceptions of Madrasah Ramah Anak (MRA), uncover their experiences in applying its principles, and identify challenges and strategies used in the process.Method – A descriptive qualitative approach was employed, involving 19 active teachers at MTs Tsamrotul Huda, Jepara. Data were collected February-April 2025 through semi-structured interviews, classroom observations, and open-ended questionnaires. Data analysis followed Miles and Huberman’s framework, which includes data reduction, data display, and conclusion drawing. To ensure accuracy and credibility, the analysis was supported by triangulation techniques. Findings – The study found varied interpretations of MRA among teachers. Around two-thirds of the participants reported consistently applying child-friendly practices through fair, participatory, and nurturing approaches. However, challenges persist, including limited facilities, safety concerns, academic pressure, and inconsistent supervision. Teachers demonstrated strong commitment to creating inclusive classrooms, with 14 out of 19 emphasizing the importance of social-emotional guidance. As one teacher expressed, “Being a child-friendly teacher means listening to students’ feelings before teaching them lessons. Research Implications – The findings underline the importance of continuous training, reflective practice, and collaboration among teachers, students, and parents. This study, however, has some limitations: it was conducted in a single school, relied on self-reported data that may be affected by social desirability bias, and showed inconsistencies between reported student participation and the teacher-focused sample. Future research should involve schools from different regions, include more varied participants, and use longitudinal observation to examine the long-term impact of child-friendly education.